Good Winner, Bad Loser: Abnormal Stock Return LQ45 Indonesia Stock Exchange During Covid-19 - Selina Fransisca; Carolina Katrin Deo Naga; Tri Ratnawati (Budapest International Research and Critics University, 2021)
This study aims to obtain data about “good winners” and “bad losers” through the abnormal return of LQ45 stocks at the Indonesian stock exchange during COVID-19. The sample of this research is the LQ45 stock index with the research period from December 2019 until September 2020. This research method is qualitative using the analysis of expected return, actual return and abnormal return. The results of this study indicate that there are differences in LQ45 share prices before and during the pandemic, during the period before the pandemic in Indonesia in the December 2019 until February 2020 stock prices were still stable, but when Covid-19 entered Indonesia in the March 2020 period, stocks price dropped. The “Good Winner” in the LQ45 stock index is Tower Bersama Infrastructure Tbk and National Syariah Pension Savings Bank Tbk, while the “Bad Loser” is Unilever Indonesia Tbk. and Mitra Keluarga Kary Saran Tbk. The form of capital market efficiency on the LQ45 stock index during this pandemic is a semi-strong for.